Drivers of Investment Interest among Students: Knowledge, Benefits, and Motivation - Erlita Kurniawaty; Fauziah Septiani (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: The aim of this research was to ascertain the level of investing knowledge, rewards, and motivation among students. Methodology: Purposive sampling technique for primary data collection was employed in which had 136 respondents students participated. Multiple regression analysis, determination coefficient test, F test, and t test were the data analysis techniques that were employed using SPSS. Findings: The analysis’s findings demonstrated that investing interest was neither positively nor significantly impacted by investment knowledge or rewards. In fact, investment interest was significantly and favorably impacted by investment motive. Implications/Novel Contribution: Universities are supposed to be able to promote students’ interest in investing by offering knowledge and resources. The study brings several policy insights for education leaders, scholars and administrators.